Emerging Research in Computing, Information, Communication and Applications ERCICA 2015, Volume 3 - Shetty, N. R.; Prasad, N. H.; Nalini, N.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This proceedings volume covers the proceedings of ERCICA 2015. ERCICA provides an interdisciplinary forum for researchers, professional engineers and scientists, educators, and technologists to discuss, debate and promote research and technology in the upcoming areas of Computing, Information, Communication and their Applications. The contents of this book cover emerging research areas in fields of Computing, Information, Communication and Applications. This will prove useful to both researchers and practicing engineers.
Keywords: Telecommunication; Application software; Image processing -- Digital techniques; Computer vision; Communications Engineering, Networks; Computer and Information Systems Applications; Computer Imaging, Vision, Pattern Recognition and Graphics